PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT. ARSYNERGY RESOURCE - Fajria Ramadani; Mei Retno Adiwati (STKIP Persada Khatulistiwa Sintang, 2022)
Human resources are an important role in achieving the goals of the company. Human resources are the main factor for management in the organization. Resources are also important things to be given more attention by the industry, because good resources by the company can make the value in the company increase and the company will achieve the desired goals. This study aims to analyze the effect of work discipline and work stress on employee performance at PT. Arsynergy Resources. This study is a quantitative study. The population in the study is 60 employees. The sampling technique used is by using a saturated sample. Methods in collecting data using a questionnaire. Analysis for data using Structural Equation Modeling (SEM) using SmartPLS software. The results of the study, obtained if the existence of good work discipline can increase the performance of employees at PT. Arsynergy Resource, and the results of the test show that if there is a work stress that is not excessive, it can certainly improve the performance of PT. Arsynergy Resources